2019
DOI: 10.2147/idr.s226612
|View full text |Cite
|
Sign up to set email alerts
|

<p>Coexistence Of Plasmid-Mediated <em>mcr-1</em> And <em>bla</em><sub>NDM-4</sub></em> Genes In A Klebsiella pneumoniae Clinical Strain In Vietnam</p>

Abstract: In this study, we characterized the first clinical Klebsiella pneumoniae strain co- harboring mcr-1 and blaNDM-4 genes in Vietnam, which was recovered from a patient admitted to hospital in 2015. This strain demonstrated nonsusceptible to all tested antibiotics, including last-line antibiotics such as carbapenems (MICs ≥128 μg/mL) and colistin (MIC =32 μg/mL), except tigecycline (MIC =1 μg/mL). Whole-genome analysis using both MinION and MiSeq data revealed that the strain carried 29 resistance genes. Particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Two carbapenemase genes, bla KPC and bla NDM , are responsible for the phenotypic resistance of 90% of carbapenem-resistant Enterobacteriaceae strains in China. 26 The co-existence of mcr and carbapenemase genes, such as bla NDM-5 , 27 bla NDM-4 , 28 bla KPC , 29 and bla OXA , 30 has been sporadically reported in different countries. In the national monitoring data from China, one report showed that the mcr-1 was detected in 4.6% (13/282) of carbapenem-resistant E. coli isolates and coexisted with New Delhi metallo-enzyme (NDM)-5 in one strain.…”
Section: Discussionmentioning
confidence: 99%
“…Two carbapenemase genes, bla KPC and bla NDM , are responsible for the phenotypic resistance of 90% of carbapenem-resistant Enterobacteriaceae strains in China. 26 The co-existence of mcr and carbapenemase genes, such as bla NDM-5 , 27 bla NDM-4 , 28 bla KPC , 29 and bla OXA , 30 has been sporadically reported in different countries. In the national monitoring data from China, one report showed that the mcr-1 was detected in 4.6% (13/282) of carbapenem-resistant E. coli isolates and coexisted with New Delhi metallo-enzyme (NDM)-5 in one strain.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, two infections were classified as XDR, and only susceptible to colistin ( n =2), and amikacin ( n =1) (). These include an ST15 carrying the carbapenemase-producing plasmid pKP27-NDM4 [aac(3)-Iid , aac(6′)-lb , aadA1 , qnrS1 , bla LAP-2 , bla OXA-9 , bla CTX-M-14 , and bla NDM-4 ; accession number: NZ_CP041642], which was previously isolated in HCMC, Vietnam [52]; and an ST17 carrying pCFI-3 [aac(6′)-lb-cr , arr-3 , bla OXA-1 , sul1 , catB3 , qnrB4 , and bla DHA-1 ; accession number: NC_019984]. The presence of bla DHA-1 in several ST17 and ST86 strains underlay their resistance to ceftriaxone and ticarcillin/clavulanate.…”
Section: Resultsmentioning
confidence: 99%
“…Two carbapenemase genes, bla KPC and bla NDM , are responsible for the phenotypic resistance of 90% of carbapenem-resistant Enterobacteriaceae strains in China [18]. The co-existence of mcr and carbapenemase genes, such as bla NDM-5 [19], bla NDM-4 [20], bla KPC [21], and bla OXA [22], has been sporadically reported in different countries. In the national monitoring data from China, one report showed that the mcr-1 gene was detected in 4.6% (13/282) of carbapenem-resistant E. coli isolates and coexisted with the New Delhi metallo-enzyme (NDM)-5 in one strain [23].…”
Section: Discussionmentioning
confidence: 99%